1986
DOI: 10.1002/jso.2930310208
|View full text |Cite
|
Sign up to set email alerts
|

Pure squamous cell carcinoma of the breast

Abstract: Pathological curiosities have always fascinated the surgical community, and management of breast cancer by the physician has, at times, revealed such rarities. A recent case of squamous cell carcinoma in a clear fluid breast cyst has prompted a review of our experience with this rare pathology, and allowed us to make the following statements: We propose that squamous cell carcinoma of the breast arises from ductal metaplasia. When the T.N.M. system is applied to the squamous cell lesion, the apparent poor prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…As rates of metastases to the axilla are variable (0–65%), 3,7,12 dissection to Level II axillary clearance is recommended 23 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As rates of metastases to the axilla are variable (0–65%), 3,7,12 dissection to Level II axillary clearance is recommended 23 12 …”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of primary SCC of the breast is variably reported, probably reflecting the fact that previous series reported more advanced tumours at presentation and subsequently, a worse prognosis 6 . Later reports are more representative and Lafreniere et al suggested a prognosis equalling infiltrating ductal cancer of up to 9 years, 23 while Cornog et al stated that there was no significant difference between the 5 year survival rate of primary SCC of the breast, and that of all kinds of breast cancer 2 . In a recent series by Cardoso et al , all tumours were diagnosed at a relatively early stage and following standard treatment there were no relapses or cancer related deaths after a mean follow‐up period of 64 months 7 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this case represents the first such tumor in our institution since the initiation of the tumor registry in 1955. Recognition of primary SCC of the breast as a separate entity was challenged for many years by some investigators (1,2]; however, recent reports have confirmed its existence distinct from adenocarcinoma of the breast with squamous cell metaplasia [5,6,10]. Several criteria are required to establish a firm diagnosis of primary SCC of the breast: (1) the infiltrating component of the breast cancer must be entirely squamous; (2) the tumor must be independent from the overlying skin; and (3) another site of SCC in the patient must be excluded […”
Section: Discussionmentioning
confidence: 99%
“…Our case fulfilled all these conditions. Furthermore, the clinical characteristics of the tumor in our patient are similar to those reported by others, including a central cystic necrotic component, overlying skin erythema, ab-sence of nodal metastases, and negative estrogen receptors [5,6]. Interestingly, the breast ultrasound suggested a solid tumor, most likely due to the thick consistency of the fluid that contained necrotic debris.…”
Section: Discussionmentioning
confidence: 99%
“…Suggested possibilities have included complete metaplasia of the glandular breast tissue (4, 7) and malignancy arising from benign skin lesions (4, 7, 8). Other possibilities have included the development of malignancy from chronic breast abscesses (9), and subcutaneous seeding following trauma to the breast (10,11). Lafreniere et a1 put forward a theory based on the embryological development of the breast (1).…”
Section: Discussionmentioning
confidence: 99%